2021
DOI: 10.3390/ijms222313136
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting MicroRNA-485-3p Blocks Alzheimer’s Disease Progression

Abstract: Alzheimer’s disease (AD) is a form of dementia characterized by progressive memory decline and cognitive dysfunction. With only one FDA-approved therapy, effective treatment strategies for AD are urgently needed. In this study, we found that microRNA-485-3p (miR-485-3p) was overexpressed in the brain tissues, cerebrospinal fluid, and plasma of patients with AD, and its antisense oligonucleotide (ASO) reduced Aβ plaque accumulation, tau pathology development, neuroinflammation, and cognitive decline in a transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Results of very recent animal studies expand this diversity by demonstrating CD36 involvement in an AD-associated blood brain barrier disruption 70 , and in an interaction with the nerve growth regulator1 (NEGR1) 71 , i.e., in AD-related mechanisms distinct from those active in the amyloid/tau pathways and/or the amyloid-β phagocytosis by microglia. Conversely, another recent report implicated a DNA transcription regulator microRNA (miRNA-485-3p) in the CD36 mediated amyloid-β phagocytosis and even suggested it as a potential AD therapeutic agent 72 . Yet our in silico analyses found no potential interplay of miRNA-485-3p and any of the five AD-related polymorphisms identified by the present whole-gene sequencing study (Table 5 ), thus implying that not all AD-related regulatory sites in CD36 gene must necessarily be located next to (and be influenced by) AD-related SNP’s.…”
Section: Discussionmentioning
confidence: 99%
“…Results of very recent animal studies expand this diversity by demonstrating CD36 involvement in an AD-associated blood brain barrier disruption 70 , and in an interaction with the nerve growth regulator1 (NEGR1) 71 , i.e., in AD-related mechanisms distinct from those active in the amyloid/tau pathways and/or the amyloid-β phagocytosis by microglia. Conversely, another recent report implicated a DNA transcription regulator microRNA (miRNA-485-3p) in the CD36 mediated amyloid-β phagocytosis and even suggested it as a potential AD therapeutic agent 72 . Yet our in silico analyses found no potential interplay of miRNA-485-3p and any of the five AD-related polymorphisms identified by the present whole-gene sequencing study (Table 5 ), thus implying that not all AD-related regulatory sites in CD36 gene must necessarily be located next to (and be influenced by) AD-related SNP’s.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐425‐5p‐HSPB8 axis induced cell apoptosis and promoted Tau phosphorylation in AD, and might act as a new therapeutic target for AD treatment 137 . In addition, miR‐485‐3p was overexpressed in the brain tissues, CSF, and plasma of patients with AD 138 . CD36 was a direct target of miR‐485‐3p 138 .…”
Section: Abnormally Expressed Ncrnas In Ad Patients In Regulating Cel...mentioning
confidence: 99%
“…CD36 was a direct target of miR‐485‐3p 138 . MiR‐485‐3p‐CD36 axis weakened the phagocytosis of Aβ in vitro and in vivo and might promote cell apoptosis in AD 138 . Table S3 summarizes all the abnormally expressed and cell apoptosis‐related miRNAs in AD patients 132–160 .…”
Section: Abnormally Expressed Ncrnas In Ad Patients In Regulating Cel...mentioning
confidence: 99%
“…AD is the most common type of dementia in the elderly, and extensive studies on AD have revealed altered miRNA expression profiles. Many miRNAs are severely dysregulated in the brains of AD patients, including miR-34c (upregulated [ 24 ]), miR-124-3p (downregulated [ 72 , 73 ]; upregulated [ 51 ]), miR-126a-3p (downregulated [ 72 , 74 ]), miR-128b (upregulated [ 53 ]), miR-132/-212 (downregulated [ 74 , 75 , 76 ]), miR-146a (upregulated [ 72 , 77 ]), miR-188-5p (downregulated [ 61 ]), miR-195 (downregulated [ 64 ]), miR-206 (upregulated [ 67 ]), miR-338-5p (downregulated [ 68 ]), and miR-485-5p (downregulated [ 75 ]) vs. miR-485-3p (upregulated [ 71 ]). Figure 1 shows growing evidence that miRNA dysregulation correlates with some major and important aspects of AD pathology that have been proven to cause cognitive impairment in animal models.…”
Section: Role Of Mirnas In Learning Memory and Cognitive Disordersmentioning
confidence: 99%
“…Mechanistically, miR-485-5p directly targeted PACS1, a hallmark of AD, in pericytes [ 70 ]. As miR-485-5p was downregulated in the prefrontal cortex of patients with late-onset AD [ 75 ], miR-485-3p was overexpressed in the brain tissues, CSF, and plasma of patients with AD [ 71 ]. Furthermore, the knockdown of miR-485-3p enhanced Aβ clearance via CD36-mediated phagocytosis, decreased truncated tau levels, and reduced the secretion of proinflammatory cytokines, including interleukin-1β and tumor necrosis factor-α, eventually alleviating cognitive decline in 5xFAD transgenic mice.…”
Section: Role Of Mirnas In Learning Memory and Cognitive Disordersmentioning
confidence: 99%